Polatuzumab Vedotin in Previously Untreated Diffuse Large B-Cell Lymphoma - Tilly, Hervé; Morschhauser, Franck; Sehn, Laurie H; Friedberg, Jonathan W; Trněný, Marek; Sharman, Jeff P; Herbaux, Charles; Burke, John M; Matasar, Matthew; Rai, Shinya; Izutsu, Koji; Mehta-Shah, Neha; et al. (The New England journal of medicine, 2022)
BACKGROUND: Diffuse large B-cell lymphoma (DLBCL) is typically treated with rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP). However, only 60% of patients are cured with R-CHOP. Polatuzumab vedotin is an antibody-drug conjugate targeting CD79b, which is ubiquitously expressed on the surface of malignant B cells. METHODS: We conducted a double-blind, placebo-controlled, international phase 3 trial to evaluate a modified regimen of R-CHOP (pola-R-CHP), in which vincristine was replaced with polatuzumab vedotin, as compared with standard R-CHOP, in patients with previously untreated intermediate-risk or high-risk DLBCL. Patients 18 to 80 years of age were randomly assigned in a 1:1 ratio to receive six cycles of either pola-R-CHP or R-CHOP, plus two cycles of rituximab alone. The primary end point was investigator-assessed progression-free survival. Secondary end points included overall survival and safety. RESULTS: Overall, 879 patients underwent randomization: 440 were assigned to the pola-R-CHP group and 439 to the R-CHOP group. After a median follow-up of 28.2 months, the percentage of patients surviving without progression was significantly higher in the pola-R-CHP group than in the R-CHOP group (76.7% [95% confidence interval (CI), 72.7 to 80.8] vs. 70.2% [95% CI, 65.8 to 74.6] at 2 years; stratified hazard ratio for progression, relapse, or death, 0.73 by Cox regression; 95% CI, 0.57 to 0.95; P = 0.02). Overall survival at 2 years did not differ significantly between the groups (88.7% [95% CI, 85.7 to 91.6] in the pola-R-CHP group and 88.6% [95% CI, 85.6 to 91.6] in the R-CHOP group; hazard ratio for death, 0.94; 95% CI, 0.65 to 1.37; P = 0.75). The safety profile was similar in the two groups. CONCLUSIONS: Among patients with previously untreated intermediate-risk or high-risk DLBCL, the risk of disease progression, relapse, or death was lower among those who received pola-R-CHP than among those who received R-CHOP. (Funded by F. Hoffmann-La Roche/Genentech; POLARIX ClinicalTrials.gov number, NCT03274492.).
Keywords: senioři; difúzní velkobuněčný B-lymfom; dvojitá slepá metoda; Doxorubicin; cyklofosfamid; Double-Blind Method; prednison; doba přežití bez progrese choroby; monoklonální protilátky; Middle Aged; mužské pohlaví; Antibodies, Monoclonal; Adult; Vincristine; Lymphoma, Large B-Cell, Diffuse; Rituximab; doxorubicin; ženské pohlaví; Cyclophosphamide; Humans; Prednisone; Progression-Free Survival; rituximab; lidé středního věku; vinkristin; Immunoconjugates; Antineoplastic Combined Chemotherapy Protocols; protokoly protinádorové kombinované chemoterapie; dospělí; imunokonjugáty; Female; Aged; lidé; Male